Lactobacillus reuteri DSM 17938 Probiotics May Increase CC-Chemokine Receptor 7 Expression in Infants Treated With for Colic - Francesco Savino; Ilaria Galliano; Andrea Savino; Valentina Daprà; Paola Montanari; Cristina Calvi; Massimiliano Bergallo (Frontiers Media S.A., 2019)
Aim: Studies have shown that Lactobacilli reuteri probiotics can affect cells that play a key role in the immune system. This in vivo Italian study investigated how Lactobacillus reuteri DSM 17938 influenced CC-chemokine receptor 7 (CCR7) and interleukin 10 (IL-10) in breastfed colicky infants.Methods: Our University hospital in Turin recruited 50 healthy outpatients, at a median age of approximately 1 month, from September 2017 to August 2018. They were randomized to daily Lactobacillus reuteri DSM17938 (1 × 108 cfu) or a placebo for 28 days from recruitment. We collected peripheral blood and evaluated the expression of CCR7 messenger ribonucleic acid using the real-time TaqMan reverse transcription polymerase chain reaction method at baseline and after the study period.Results: We found increased expression of CC-chemokine receptor 7 in infants treated with the probiotic, but not the controls (p < 0.0026). No differences were observed for interleukin 10 after the study period in either group. At baseline, daily crying time was comparable in the probiotic and control groups: 341 (25) vs. 337 (29) min., respectively (p = 0.450). After 28 days, daily mean crying time decrease statistically in the probiotic group: 78 (23) vs. 232 (31), respectively (p < 0.001).Conclusion: The increase in CC-chemokine receptor 7 might have been a response to probiotic treatment. As a relatively small sample was used to conduct this study, our research needs to be replicated in different settings, and over time, to produce comparable findings.